Moving towards global satellite based products for monitoring of inland and coastal waters. Regional examples from Europe and South America - Spyrakos, E.; Hunter, P.; Simis, S.; Neil, C.; Riddick, C.; Wang, S.; Varley, A.; Blake, M.; Groom, S.; Palenzuela, J Torres; Gonzalez, L. Vilas; Cardenas Mansilla, Carlos Alberto; et al. (My University, 2020)
Surface waters are a fundamental resource. They fulfil key function in global biogeochemical cycles and are core to our water, food and energy security. The rapidly increasing rate of data collection from different Earth observation (EO) missions suitable for observing water bodies has promoted satellite remote sensing (RS) as a more widely recognised source of information on a number of indicators of water quality and ecosystem condition at local and global scales. In parallel, advances in optical sensors support new and more detailed characterisation of the Earth surface and could lead to innovative EO-based products. Nonetheless, RS of water colour of inland and coastal systems, especially in larger scales and over long-term time series, faces unique challenges. This study provides an overview of the challenges and solutions of developing a global observation platform, including the diverse and complex optical properties of inland waters and guided algorithm selection procedure required to deliver reliable data. The development and validation of a global satellite data processing chain (Calimnos) has been supported by access to an extensive in situ data from more than thirty partners around the world that are now held in the LIMNADES community-owned database. This approach has resulted in a step-change in our ability to produce regional and global water quality products for optically complex waters. Local examples of the data outputs will be explored and the opportunities in how these data can be embedded within local and national monitoring schemes to facilitate better management of water will be discussed.
Keywords: coastal waters; global products; lakes; patagonian fjords; remote sensing